2021
DOI: 10.3389/fmars.2021.639608
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometry of Seabream in a Sea-Cage: Is Acceleration a Good Proxy for Activity?

Abstract: Activity assessment of individual fish in a sea-cage could provide valuable insights into the behavior, but also physiological well-being and resilience, of the fish population in the cage. Acceleration can be monitored continuously with internal acoustic transmitter tags and is generally applied as a real-time proxy for activity. The objective of this study was to investigate the activity patterns of Gilthead seabream (Sparus aurata) by transmitter tags in a sea-cage and analyze correlations with water temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The low VAR m during progressive hypoxia, and absence of differences between fish in the tank and respirometers, presumably indicates that movements in the tank did not involve changes in speed, which are necessary to engender variation in acceleration (Hinch et al, 2002;Kawabe et al, 2003;Palstra et al, 2021;Tanaka et al, 2001). Thus, the gentle movements observed during hypoxia in the tank were clearly below the sensitivity of the accelerometer in the tag.…”
Section: Responses To Hypoxiamentioning
confidence: 95%
See 1 more Smart Citation
“…The low VAR m during progressive hypoxia, and absence of differences between fish in the tank and respirometers, presumably indicates that movements in the tank did not involve changes in speed, which are necessary to engender variation in acceleration (Hinch et al, 2002;Kawabe et al, 2003;Palstra et al, 2021;Tanaka et al, 2001). Thus, the gentle movements observed during hypoxia in the tank were clearly below the sensitivity of the accelerometer in the tag.…”
Section: Responses To Hypoxiamentioning
confidence: 95%
“…The metabolic costs of such movements are paid during recovery, rather than during the activity itself (Webb, 1978;Kieffer, 2000), so changes in f H may have been out of phase with changes in VAR m . Palstra et al (2021) concluded that acceleration was most reliable as an index of unsteady burst swimming activity in the seabream; for example, when fish are feeding. Although measures of body acceleration have also been used to predict metabolic rate in fish (Bouyoucos et al, 2017;Gleiss et al, 2010;Metcalfe et al, 2016;Wilson et al, 2013;Wright et al, 2014), it seems unlikely this will ever have the same predictive power as f H , not least because movement is only one component of metabolic activity in fish.…”
Section: Relationships Of F H To Acceleration and Metabolic Ratementioning
confidence: 99%
“…The above findings reinforce the need of further research addressing the type of body movements that are recorded from the externally or internally implanted fish sensors. Certainly, Palstra et al (2021) pointed out that gilthead sea bream accelerations from acoustic transmitter tags (ventrally implanted) are a good proxy of unsteady swimming activity (e.g., escape reactions and aggressive or foraging behavior) in experimental sea cages, but not of sustained swimming exercise. This assumption is based on the correlations between accelerations and the weight of heart and mesenteric fat weight, which were the opposite to that found and expected in exercised training fish (Blasco et al, 2015;Rodnick and Planas, 2016;Palstra et al, 2020).…”
Section: Evaluating How Is Fish Sensing and Responding Problems And P...mentioning
confidence: 99%
“…Acoustic telemetry techniques have been used in aquaculture for chinook salmon (e.g., Cubitt et al, 2003), Atlantic salmon (e.g., Føre et al, 2011Føre et al, , 2017, Atlantic cod (e.g., Rillahan et al, 2011;Ward et al, 2012), and gilthead seabream (e.g., Muñoz et al, 2020;Palstra et al, 2021). These studies have focused on monitoring fish positioning and behaviour in commercial sea pen settings.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy and reliability of a three-dimensional system was tested on chinook salmon (Cubitt et al, 2003). Further, acoustic telemetry has been used to infer behaviour, including vertical positioning and diel swimming patterns in farmed fish (e.g., Føre et al, 2011Føre et al, , 2017Rillahan et al, 2011;Ward et al, 2012;Muñoz et al, 2020;Palstra et al, 2021). Individual fish tags do not capture the entire pen population, but they provide access to data on individual fish (e.g., swimming speed) that is not available when using population-level echosounding.…”
Section: Introductionmentioning
confidence: 99%